Dissipation Kinetics and Safety Evaluation of Flonicamid in Four Various Types of Crops - Tao Zhang; Yue Xu; Xuan Zhou; Xiaojie Liang; Yang Bai; Fengshou Sun; Wenwen Zhang; Ning Wang; Xiuyu Pang; Yuekun Li (Molecules, 2022)
The chemical insecticide flonicamid is widely used to control aphids on crops. Differences among crops make the universality of detection methods a particularly important consideration. The aim of this study was to establish a universal, sensitive, accurate and efficient method for the determination of flonicamid residues in peach, cucumber, cabbage and cotton. QuEChERS pretreatment was combined with ultrahigh-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). A satisfactory recovery rate of 84.3–99.3% was achieved at three spiking levels, and the relative standard deviation (RSD) was 0.41–5.95%. The limit of quantification (LOQ) of flonicamid in the four matrices was 0.01 mg/kg. The residue and dissipation kinetics of flonicamid in four types of crops in various locations were determined by using the optimized method. The results showed that flonicamid had a high dissipation rate in the four different types of crops and a half-life in the different matrices and locations of 2.28–9.74 days. The terminal residue of flonicamid was lower than the maximum residue limit (MRL). The risk quotient (RQ) of flonicamid was 4.4%, which is significantly lower than 100%. This result shows that the dietary risk presented by using flonicamid at the maximum recommended dose is low and acceptable. The comprehensive long-term dietary risk assessment of flonicamid performed in this study provides a reference for the protection of consumer health and safe insecticide use.